Agronomic strategies to enhance the early vigor and yield of maize part II: the role of seed applied biostimulant, hybrid, and starter fertilization on crop performance - Capo, Luca; Sopegno, Alessandro; Reyneri, Amedeo; Ujvári, Gergely; Agnolucci, Monica; Blandino, Massimo (Frontiers in Plant Science, 2023)
Maize cropping systems need to be re-designed, within a sustainable intensification context, by focusing on the application of high-use efficiency crop practices, such as those that are able to enhance an early plant vigor in the first critical growth stages; such practices could lead to significant agronomic and yield benefits. The aim of this study has been to evaluate the effects of the cultivation of hybrids with superior early vigor, of the distribution of starter fertilizers at sowing, and of the seed application of biostimulants on promoting plant growth and grain yield in full factorial experiments carried out in both a growth chamber and in open fields. The greatest benefits, in terms of plant growth enhancement (plant height, biomass, leaf area) and cold stress mitigation, were detected for the starter fertilization, followed by the use of an early vigor hybrid and a biostimulant seed treatment. The starter fertilization and the early vigor hybrid led to earlier flowering dates, that is, of 2.1 and 2.8 days, respectively, and significantly reduced grain moisture at harvest. Moreover, the early vigor hybrid, the starter NP fertilization, and the biostimulant treatment increased grain yield by 8.5%, 6.0%, and 5.1%, respectively, compared to the standard hybrid and the untreated controls. The combination of all the considered factors resulted in the maximum benefits, compared to the control cropping system, with an increase in the plant growth of 124%, a reduction of the sowing-flowering period of 5 days, and a gain in grain yield of 14%. When choosing the most suitable crop practice, the diversity of each cropping system should be considered, according to the pedo-climatic conditions, the agronomic background, the yield potential, and the supply chain requirements.